The way things work. Friction [videorecording (DVD)] - Macaulay, David (Schlessinger Media, 2003)
Two young Mammoth Islanders are delivering mail with a mammoth-drawn wagon when they learn how important the force of friction is as they attempt to slow down. They test a variety of brakes to find the type just right for them, but even with proper brakes, they still get an unscheduled bath after a failed attempt to stop quickly.